2016
DOI: 10.18632/oncotarget.11580
|View full text |Cite
|
Sign up to set email alerts
|

Novel multiple tyrosine kinase inhibitor ponatinib inhibits bFGF-activated signaling in neuroblastoma cells and suppresses neuroblastoma growth in vivo

Abstract: Neuroblastoma (NB) is one of the most common pediatric malignancies in children. Abnormal activation of receptor tyrosine kinases contributes to the pathological development of NB. Therefore, targeting tyrosine kinase receptors to cure NB is a promising strategy. Here, we report that a multi-targeted tyrosine kinase inhibitor ponatinib inhibited NB cell proliferation and induced NB cell apoptosis in a dose-dependent manner. In addition, ponatinib suppressed the colony formation ability of NB cells. Mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…The soft agar assay was performed as previously described4445. Briefly, a 5% (w/v) base agar layer was made by adding agar (214220, Difco Laboratories, Detroit, MI, USA) into distilled water and then autoclavingthe mixture for 50 min before cooling in a 56 °C water bath.…”
Section: Methodsmentioning
confidence: 99%
“…The soft agar assay was performed as previously described4445. Briefly, a 5% (w/v) base agar layer was made by adding agar (214220, Difco Laboratories, Detroit, MI, USA) into distilled water and then autoclavingthe mixture for 50 min before cooling in a 56 °C water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been suggested that the use of reduced doses of ponatinib (down to 15 mg/day instead of the usual dosage of 45 mg/day) might maintain therapeutic activity in most patients while decreasing the vascular adverse events (24,26). Although clinicians will have to tackle the side effects observed upon ponatinib administration, the results achieved through our study, as well as others (17,18), indicate that this drug has the potential to be employed in clinical trials aimed to evaluate benefits in high-risk NB patients.…”
Section: Discussionmentioning
confidence: 49%
“…Although we could not prove a significant activity of axitinib in our in vivo model, one previous study indicated that axitinib could partially impair the growth of human NB xenografts by inhibiting angiogenesis (16). Notably, independent investigations have very recently proposed ponatinib itself as a drug displaying antitumor efficacy against NB (17,18). Ponatinib proved to inhibit the FGFR1-activated signaling pathway and enhance the cytotoxic effects of doxorubicin on NB cells (18).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study, we report for the first time that a novel combination of drugs, the BRAF inhibitor PLX4720 and the FDA-approved multitarget TK inhibitor ponatinib, synergistically reduces p-MEK and p-ERK compared with single-drug treatments in BRAF V600E cells. The chemoresistance of ponatinib has been frequently raised as critical issues in the preclinical and clinical settings; this might result in lower effect of ponatinib in vivo compared with in vitro study (31).…”
Section: Discussionmentioning
confidence: 99%